Penerapan Media Animasi Film Pendek pada Pembelajaran Teks Cerita Wayang Mahabarata untuk Peserta Didik Kelas X Akl 3 SMKN 1 Kendal - Farazila, Nurya; Sulanjari, Bambang; Werdiningsih, Yuli Kurniati (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2025)
The purpose of this study is to describe "The Application of Short Film Animation Media in Learning the Mahabharata Wayang Story Text for Class X AKL3 Students of SMKN 1 Kendal. This study was motivated by the fact that there are still many students who found that a number of students still have difficulty in listening to literary works, especially in learning the Mahabharata Wayang Story Text. Short film animation media in learning the Mahabharata Wayang Story Text emerged as an interesting alternative. This study is included in quantitative research. Two variables commonly used in quantitative research are independent variables and dependent variables. The sampling technique used is purposive sampling. Data collection used in this study includes test and non-test techniques. The results of the study obtained after data analysis are as follows: The results of student scores obtained from the knowledge and skills aspects, the results of the study explain that out of 35 students, 29 students have completed with a percentage of 83% and 6 students with a percentage of 17% have not completed. The average value obtained from student learning outcomes is 79.2, which is higher than the KKM value of 70. Thus, the application of short film animation media in learning the Mahabharata puppet story text for class X AKL3 students of SMKN 1 Kendal can have an influence on learning achievement.